Synthetic control on structure/dimensionality and photophysical properties of low dimensional organic lead bromide perovskite - Haris, Muhammed P. U.; Bakthavatsalam, Rangarajan; Shaikh, Samir; Kore, Bhushan P.; Moghe, Dhanashree; Gonnade, Rajesh G.; Sarma, D. D.; Kabra, Dinesh; Kundu, Janardan (Inorganic chemistry, 2018)
Low dimensional lead halide perovskites have attracted huge research interest due to their structural diversity and remarkable photophysical properties. The ability to controllably change dimensionality/structure of perovskites remains highly challenging. Here, we report synthetic control on structure/dimensionality of ethylenediammonium (ED) lead bromide perovskite from a two dimensionally networked (2DN) sheet to a one dimensionally networked (1DN) chain structure. Intercalation of solvent molecules into the perovskite plays a crucial role in directing the final dimensionality/structure. This change in dimensionality reflects strongly in the observed differences in photophysical properties. Upon UV excitation, the 1DN structure emits white light due to easily formed “self-trapped” excitons. 2DN perovskites show band edge blue emission (∼410 nm). Interestingly, Mn2+ incorporated 2DN perovskites show a highly red-shifted Mn2+ emission peak at ∼670 nm. Such a long wavelength Mn2+ emission peak is unprecedented in the perovskite family. This report highlights the synthetic ability to control the dimensionality/structure of perovskite and consequently its photophysical properties.

Ligand structure directed dimensionality reduction (2D -> 1D) in lead bromide perovskite - Bakthavatsalam, Rangarajan; Haris, Muhammed P. U.; Shaikh, Samir R.; Lohar, Amruta; Mohanty, Ashutosh; Moghe, Dhanashree; Sharma, Shivani; Biswas, Chinmoy; Raavi, Sai Santhosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Physical Chemistry C, 2020)
Low dimensional (2D, 1D) lead halide perovskites are currently attracting huge research interest due to their enabling properties. Demonstrating synthetic control on the dimensionality/ structure of these perovskites is highly challenging. Dimensionality in these perovskites is largely dictated by the nature/structure and composition of the incorporating ligands and the utilized synthetic conditions. Here, we demonstrate chemical composition based control on reduction of dimensionality (2D -> 1D) for lead bromide perovskite utilizing 2-(2-aminoethyl)isothiourea dihydrobromide as a common precursor ligand (Isothio Bromide). Controlling the hydrothermal reaction parameters (temperature, time) at a fixed precursor ratio affords corner-shared, contorted 2D sheet perovskite and corner-shared, contorted, chiral 1D chain perovskite. Such dimensionality reduction leads to contrasting photophysical properties: 1D chain perovskite shows long-lived and self-trapped broad band emission, whereas 2D perovskite shows short-lived, band edge emission with a long tail. Mechanistic studies and single crystal structure analysis reveal the incorporation of the utilized precursor ligand (Isothio Bromide) in 2D perovskite. Surprisingly, the 1D perovskite is found to be chiral (P2(1) space group) incorporating 2-(2-aminoethyldisulfanyl)ethanamine and ammonium ions as the achiral ligands generated in situ due to hydrothermal cleavage of the precursor (Isothio Bromide) ligand. Such structural and compositional change of the ligands, which manifests a different hydrogen bonding network in the resultant perovskite structure, plays a decisive role in dictating the final molecular formula and dimensionality/structure of the perovskite which largely controls their photophysical properties.